About the Code: General Theoretical Aspect - Vladimir Valentinovich Kozhevnikov (Britain International for Academic Research (BIAR-Publisher), 2021)
The article discusses a number of problems related to such a normative legal act as a code: its concept, increasing the proportion, correlation with other laws. Particular attention is paid to the situation according to which the code is a